Assessment of the Osseointegration of Pure-Phase β-Tricalcium Phosphate (β-TCP) Ceramic Cylinder Implants in Critical Segmental Radial Bone Defects in Rabbits - Daniel Cardoso Garcia; Larissa Eckmann Mingrone; Felipe Eduardo Pinotti; Leonardo Seade; Rosane de Melo; Ademar Benévolo Lugão; José Artur Brilhante Bezerra; Marcelo Jorge Cavalcanti de Sá (Veterinary Sciences)
Autografts, allografts, and synthetic bone substitutes are essential in reconstructive orthopedic surgery. Although autografts and allografts provide excellent skeletal integration, their use is limited by host morbidity and graft acquisition challenges. Synthetic materials like β-tricalcium phosphate (β-TCP) offer promising osseoconductive properties as a potential substitute. This study evaluated the osseointegration of β-TCP ceramic cylinder implants in bone defects in rabbits. Eighteen New Zealand rabbits underwent radial diaphysis ostectomy to create a critical segmental defect and were divided into three groups: Group A received β-TCP blocks, Group B received allogenous cortical bone grafts, and Group C underwent ostectomy without defect filling. Postoperative assessments included clinical evaluations, radiographs, micro-computed tomography, and histology at various time points to assess osseointegration and implant resorption. At the 120th postoperative day, Group B showed successful bone integration without infection. In contrast, Group A showed no osseointegration or resorption of the β-TCP implants, and Group C exhibited bone non-union. While β-TCP demonstrated biocompatibility, it lacked osseoconductivity, likely due to low porosity. β-TCP implants did not promote bone consolidation, suggesting that further research on porosity and shape is needed to improve their suitability for veterinary orthopedic reconstructive surgery.